Polypoid Endometriosis of Cervix: A Case Report - Syed Asif Hashmi; Yashika Bhatia; Sanjay Singh (Gynecology Obstetrics & Reproductive Medicine)
Polypoid endometriosis is an uncommon and distinctive variant of endometriosis with histologic features simulating those of an endometrial polyp which is found most often in the colon and ovary. The cervix is an infrequent site for polypoid endometriosis. We report a 40-year-old female presented with irregular bleeding and on examination detected to have an endocervical polyp. She underwent polypectomy and histopathological examination suggested polypoid endometriosis. She remained asymptomatic during two years of follow-up. Polypoid endometriosis is a variant of endometriosis that may be mistaken for a neoplasm on clinical and pathologic examination. There is often a delay in diagnosis resulting in unnecessary suffering and reduced quality of life. Though a rare entity, it should be considered in the differential diagnosis of all cervical polyp.